Affinity Chromatography Methods and Protocols (Third Edition) - Reichelt, Senta (Springer, 2015)
The ongoing progress in biomedicine (e.g., identification of low abundant proteins in human blood) requires high standards of bioseparation and purification techniques. Affin ity chromatography is one of the most selective and versatile types of liquid adsorption chromatography and is particularly suited for sophisticated purification processes. Notably, the concept of affinity chromatography is not a new state-of-the-art development. The first report on affinity chromatography-based separations was already published in the early 1900s. The Thomson Reuters database reveals more than 150,000 publications or reports including the term “affinity chromatography.” The number of publications is still increas ing exponentially. The significance and timeliness of the topic are illustrated by the fact that more than 17,000 scientific articles, reports, or patents in English language were published since 2010 on this very field....